Aloe (Aloe vera) cultivation technology and medicinal properties - Jumayeva Dinora Omon qizi (Zien Journals, 2023)
In this article, the medicinal properties of the aloe plant, its importance in folk medicine and economy, and its chemical composition are explained
Keywords: Aloe barboadensis; South-Eastern Africa; aloin